GEMBIRA BERMAIN MUSIK: PENERAPAN MODEL QUANTUM LEARNING DALAM PEMBELAJARAN SENI MUSIK DI SEKOLAH DASAR - Karsono, Karsono (Mimbar Sekolah Dasar, 2016)
The purpose of this study was to improve the quality of learning music in elementary school, particularly in promoting a fun learning atmosphere for students. Subjects were students in grade IV SDN Baturetno 1 Wonogiri. This study uses classroom action research, which combines both of quantitative approach and qualitative, to determine the level of students' affective reactions on the application as a quantum learning model. Source of data is collected by the technique of giving questionnaires, observations, and interviews. Test the validity use the technique of source triangulation and methods. Analysis was done by descriptive-comparative. From the findings, it seemed that the application of quantum learning on music class in elementary school, could increase fun learning atmosphere for students. Level affective reactions experienced by students showed 97% of students to the level of pleasure, 3% of students to the level of mediocre, and there is no reaction was not happy. However, the development still needs to be done primarily in the addition to the use of learning media to be combined with quantum models.Keywords: affective reactions, learning music, quantum models.